Single-cell hemoprotein (heme-SCP) exerts the prebiotic potential to establish a healthy gut microbiota in small pet dogs - Lee, Seungki; Choi, Ahyoung; Park, Kyung Hoon; Lee, Seoyeon; Yoon, Hyunjin; Kim, Pil (Food Science and Biotechnology, 2023)
To investigate the effect of the single-cell hemoprotein (heme-SCP) source on animals, a dog-treat (100 g for each dog) harboring 0.2% heme-SCP was manufactured and fed to seven pet dogs (< 10 kg) in a randomized manner (irrespective of owner’s feeding style, dogs’ health conditions, and staple diets), and the feces before and after the dog-treat diet were analyzed to define the structure of the microbiota. The total bacterial species of the seven dogs showed no difference (564–584), although the bacterial compositions varied significantly. The Firmicutes phylum increased (54.7–73.7%), showing differential species composition before and after heme-SCP intake. Proteobacteria, Bacteroidetes, and Fusobacteria decreased (5.4–3.8%, 32.9–16.8%, and 6.3–3.6%, respectively), which agreed with the previous observation of deliberate feeding. Therefore, it is conceivable that heme-SCP as a prebiotic can shape the gut microbiota regardless of the administration method.
Keywords: Bacterial community; Dog; Gut microbiota; Health condition; Heme-SCP; Hemoproteins; Pet dogs; Prebiotics; Single cells; Single-cell hemoprotein; Bacterial community; Dog; heme-SCP; Prebiotics; Single-cell hemoprotein